Compliance In Early Childhood (Ages 5-6 Years) In School and Home Settings - Dwi Nurhayati Adhani; Fikri Nazarullail (Universitas Muhammadiyah Ponorogo, 2020)
This research examined compliance in early childhood with an age range between 5-6 years in TK X Bangkalan. Compliance is a behavior that early children need to have. Compliance is necessary for children to follow the rules set. The rules can be different in school settings and home settings, but there are several forms of rules that are almost the same in both settings. Rules are set by teachers and parents so that children can be more disciplined and independent. Compliance cannot be achieved instantly in shaping early childhood behavior, but it requires a process. This research aimed to see compliance reflected through concrete behavior in two settings and to see what kind of behavior children do when obeying the rules. The results of this research showed that early childhood compliance formed behaviors at school and at home, such as taking off shoes, putting bags in place, greeting teachers and parents. This research used a quantitative research approach with descriptive research type. Determination of population and sample were done by purposive sampling, namely TK YKK1 Kab. Bangkalan with a total of 30 respondents of children. Data analysis was performed using SPSS and the results were obtained that child compliance in home and school settings had a medium category. The medium category means that the child has an obedient attitude towards the rules at home or school but there are several aspects, the child violates the rules applied by the school and home environment.